Passive, Active, and Proactive Systems and Machines for the Protection and Preservation of Animals and Animal Species - Bendel, Oliver (Frontiers in Animal Science, 2022)
Digitalization and automation are expanding into many areas, resulting in more widespread use of partially and fully autonomous machines and robots. At the same time, environmental and other crises and disasters are on the rise, the world population is growing, and animals are losing their habitat. Increasingly, machines and robots such as agricultural vehicles, autonomous cars, robotic lawnmowers, or social robots are encountering animals of all kinds. In the process, the latter are injured or killed. Some machines can be designed so that this does not happen. Relevant disciplines and research areas briefly introduced here are machine ethics, social robotics, animal-machine interaction, and animal-computer interaction. In addition, animal welfare is important. Passive and active machines – as they are called in this review – are already appearing and help to observe and protect animals. Proactive machines may play a role in the future. They could use the possibilities of full automation and autonomy to save animals from suffering in agriculture or in the wild. During crises and disasters and in extensive nature reserves, they could observe, care for, and protect animals. The review provides initial considerations on active, passive, and proactive machines and how they can be used in an animal preservation context while bearing in mind recent technical and global developments.